EFFECT OF METHYL JASMONATE ON Bt COTTON (Gossipium hirsutam .L) GENE EXPRESSION AND MORTALITY OF PINK BOLL WORM (Pectinophora gossypiella) - J. N. Ahmad; 2; D. Majeed; M. Arshad; M. A. Malik; A. Ali; S. Nadeem; S. J. N. Ahmad; 2 (Journal of Animal and Plant Sciences, 2021)
Transgenic cotton was improved genetically by introducing bacterium Bacillus thuringiensis to produce Bt δ-endotoxins to kill the key pests of Lepidoptera. However, with passage of time low expression of Cry1Ac gene limited the glory of Bt technology. The phytohormones are key regulators of plant defense systems against the insect pests. It was noted that the defense systems of plants were significantly regulated by Salicylic acid (SA) and Methyl Jasmonate (MeJA). Particularly, Methyl Jasmonate induces proteinase inhibitors and interferes with insect digestion and feeding capability. The experiment was conducted to evaluate the effect of MeJA to induce proteinase inhibitors and Cry1Ac genes in Bt cotton cultivars and subsequently the mortality of three different populations of Pectinophora gossypiella. The two concentration of MeJA (0.25 mM and 0.5 mM) were sprayed exogenously foliar on five Bt and one non Bt cotton cultivars at the stage of bud and flower formation. The results of bioassay depicted that when plants were treated with a concentration of 0.5 mM MEJA, a significant mortality (66 to 78%) of early 3rd instar larvae of P. gossypiella was observed for field and resistant population whereas up to 89% mortality was noted for lab susceptible population as compared to very low mortality observed for not treated plants. Similarly, RT-PCR and ELISA tests showed the enhanced level of Cry1Ac gene expression and its protein (1.33-2.89 µg/g) in MeJA treated plants. In conclusion, the application of MeJA can be a suitable strategy to enhance natural defense system of plant as well as to improve the expression of Cry1Ac which cause higher mortality for the resistant and susceptible population P. gossypiella.
Keywords: Jasmonic acid; synergistic effect; Transgenic Cotton; Pectinophora gossypiella; Cry1Ac; Gene expression